(3GdLhgQI GdfajSI aj Ydhe GdcfjSIs (3ef cJH GdJQGK GdbHWj GdWbSj GdgGeIs - (3Hf RcQjG, jhMfGs; (3eJChSs; (3EScfOQ, ejNGFjd ecSjs ((3GdbGgQIs (3ecJHI GdeMHIs, 2001)
(3gh ehShYI cGedI JVe (B115 (3HGHG, hJJVef ehVhYGJ WbSjI hYbjOjI hQhMjI hJGQjNjI hJaSjQjIhZjQgG ef GdCehQ GdgGeI hdPdc agh jYO ef cJH GdfQGK GdbHWj GdgGeI hef Hjf Cge cJGHGJ YdeGA GdcfjSI GdeUQjI aj GdbQf (B13 (3e hgh CjVG eQBI UGObI dWbhS Jdc GdaJQI aj eUQs
(3ehLg ddNOGe hGdOGQSjf hGdTYHs
1 2 13 18 20 21 22
Keywords: (3GdWbhS GdeSjMjIs; (3GdYbGFO GdeSjMjIs; (3GdeSjMjIs -- (3eJaQbGJs